The async-first playbook : remote collaboration techniques for agile software teams - Moghe, Sumeet Gayathri (Addison-Wesley, 2024)
Distributed work is now inevitable, but conventional agile approaches are too "synchronous" for today's remote teams. Meetings, ceremonies, and rituals can become unsustainable when teams are scattered across the globe. The result: burnout, constant interruptions, a lack of deep work, poor work-life balance, greater frustration, and workplaces with poor diversity. In The Async-First Playbook, Thoughtworks Principal Product Manager Sumeet Gayathri Moghe provides tools and techniques to embed remote-native, asynchronous practices into traditional agile methods, making remote work more efficient, inclusive, thoughtful, and fun. Drawing on extensive experience leading distributed teams, Moghe addresses the "nuts and bolts" of specific practices and the crucial "softer" elements such as culture, mindset, and leadership. Short, practical chapters show how to adapt traditional agile techniques such as sprints and pair programming for the realities of today's distributed environments. Whatever your project, youll learn how to create asynchronous environments that promote success, improve the workplace experience, and deliver better results.